Vzácná příčina obstrukčního ikteru u mladého pacienta - Kundratová, Marie (Vnitrni lekarstvi, 2022)
In this case report is discussed the diagnosis of papillary carcinoma in the case of a patient in whose age the occurrence of the disease is very rare. The patient underwent a series of non-invasive and invasive examinations, the results of which eventually led to a surgical solution of the suspected lesion (Wipples procedure). Histological examination of the resection confirmed mixed type ampular adenocarcinoma. In the context of this finding, the results of the examination, their information value, interpretation and mutual interaction are discussed. In the postoperative period, the patient suffered from gastrointestinal bleeding, subileum and poor postoperative healing. After hospitalization, the patient was transferred to oncology care and indicated for genetic testing.
Keywords: Jaundice; Adenomatous Polyposis Coli; obstructive icterus; Common Bile Duct Neoplasms; Whipple procedure; carcinoma of the papilla of Vater; lidé; nádory ductus choledochus; familiární adenomatózní polypóza; Ampulla of Vater; Adenocarcinoma; familial adenomatous polyposis; adenokarcinom; žloutenka; ampulla Vateri; Humans